1997
DOI: 10.1152/advances.1997.273.6.s55
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions and learning outcomes of computer-assisted versus traditional instruction in physiology.

Abstract: This study compared student perceptions and learning outcomes of computer-assisted instruction against those of traditional didactic lectures. Components of Quantitative Circulatory Physiology (Biological Simulators) and Mechanical Properties of Active Muscle (Trinity Software) were used to teach regulation of tissue blood flow and muscle mechanics, respectively, in the course Medical Physiology. These topics were each taught, in part, by 1) standard didactic lectures, 2) computer-assisted lectures, and 3) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 2 publications
0
22
0
6
Order By: Relevance
“…Previous research has suggested that undergraduate students consider learning to occur when an "expert "transmits factual knowledge and not when it is constructed via problem-based learning (Biley & Smith, 1999). Additionally, previous findings have indicated that students perceive traditional lecture to be more effective compared to active learning methods even though students' learning outcomes were found to be higher in active learning courses (Lake, 2001;Richardson, 1997). Research on the use of student-centered teaching within engineering has also found that students feel that less content is covered when inductive teaching is used when compared to deductive lecture-based approaches (Yadav, Shaver, & Meckl, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that undergraduate students consider learning to occur when an "expert "transmits factual knowledge and not when it is constructed via problem-based learning (Biley & Smith, 1999). Additionally, previous findings have indicated that students perceive traditional lecture to be more effective compared to active learning methods even though students' learning outcomes were found to be higher in active learning courses (Lake, 2001;Richardson, 1997). Research on the use of student-centered teaching within engineering has also found that students feel that less content is covered when inductive teaching is used when compared to deductive lecture-based approaches (Yadav, Shaver, & Meckl, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Somit können Kapazitäten und Ressourcen auf Seiten des Lehrkörpers vermehrt für praktische Anwendungen genutzt werden. Zudem haben die Multimediaapplikationen einen höheren Wirkungsgrad [1,13] als die traditionellen Weiterbildungsmaßnahmen, was die tatsächliche und dauerhafte Vermittlung von medizinischen Inhalten anbelangt [9,10]. Dies ist durch die höhere Einprägsamkeit aufgrund der Verknüpfung akustischer und visueller Informationen bedingt, wie durch den Einsatz bewegter Bilder im Sinne von Videos und Animationen [5,19].…”
Section: Diskussionunclassified
“…Zudem haben "traditionelle" Weiterbildungsmaßnahmen einen geringeren "Wirkungsgrad" [3,16], was die tatsächliche und dauerhafte Vermittlung von Inhalten anbelangt, als z. B. sog.…”
Section: Diskussionunclassified
“…Die multimediale CD-ROM wurde anderen traditionelleren Medien wie Kongressband oder Video eindeutig vorgezogen. Eine solche Einschätzung konnte auch in anderen Untersuchungen [13,16], bei denen allerdings Lehrbuchwissen traditionell bzw. computergestützt vermittelt und anhand von Prüfungsergebnis-sen verifiziert wurde, gewonnen werden.…”
Section: Diskussionunclassified